Method for manufacturing fine cellulose fiber

JP2025021935APending Publication Date: 2025-02-14MARUSUMI PAPER

Patent Information

Application Number
JP2023126054
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-02
Publication Date
2025-02-14

AI Technical Summary

Benefits of technology

【0009】 本発明によれば、水分散液の全光線透過率が高いパルプを用いた、新たな微細セルロース繊維の製造方法を提供可能である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025021935000008
    Figure 2025021935000008
  • Figure 2025021935000009
    Figure 2025021935000009
  • Figure 2025021935000001
    Figure 2025021935000001
Patent Text Reader

Abstract

To provide a new method for manufacturing a fiber cellulose fiber using a pulp having high total light transmittance of an aqueous dispersion.SOLUTION: A method for manufacturing a fiber cellulose fiber includes a chemical treatment step of bringing a pulp with a reaction liquid containing a sulfamic acid and urea, reacting the mixture at 120°C to 180°C, and thereby substituting at least a part of a hydroxyl group of cellulose constituting the pulp with a sulfate group, and a fining treatment step of fining the pulp after the chemical treatment step, and obtaining a fine cellulose fiber, wherein in the reaction liquid, a blended amount of the sulfamic acid is 10 mmol to 48 mmol per 1 g of the pulp, a molar ratio S:U of the sulfamic acid (S) and the urea (U) is 1:0.4 to 1:1.61, and the pulp after the chemical treatment step has a cellulose I type crystal structure, and has a degree of crystallization of 76% or less and total light transmittance of a dispersion liquid dispersed in water at solid content concentration of 1 mass% of 80% or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing fine cellulose fibers. [Background technology]

[0002] Cellulose nanofibers (CNF) are microfibers with a fiber width of several to tens of nm and a fiber length of several hundred nm, which are made by nano-processing (mechanical fiberization, TEMPO catalytic oxidation, etc.) plant-derived cellulose. CNFs are lightweight, highly elastic, high strength, and have low linear thermal expansion. For this reason, composite materials containing CNFs are expected to be used in a variety of fields, including not only industrial fields but also food and medical fields.

[0003] When mechanically defibrating CNF, a large amount of energy is required to obtain CNF because the cellulose fibers are strongly bonded with hydrogen bonds. In addition, the obtained CNF has problems such as uneven fiber length.

[0004] Therefore, a manufacturing method has been developed in which a chemical treatment step is carried out to disintegrate the cellulose fibers that make up the pulp to a certain degree before carrying out the mechanical fiberization step (Patent Documents 1 to 4). This manufacturing method makes it possible to obtain CNFs with less energy than a manufacturing method in which pulp is directly mechanically treated. Moreover, it has the advantage of being able to suppress the variation in size of the obtained CNFs. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2017-43677 A [Patent Document 2] JP 2017-8472 A [Patent Document 3] JP 2017-25240 A [Patent Document 4] JP 2017-25468 A Summary of the Invention [Problem to be solved by the invention]

[0006] The present inventors have developed a new pulp that has a high total light transmittance in its aqueous dispersion. However, a method for obtaining fine cellulose fibers such as CNF by defibrating this new pulp has not yet been established.

[0007] Therefore, an object of the present invention is to provide a new method for producing fine cellulose fibers using pulp having a high total light transmittance in an aqueous dispersion. [Means for solving the problem]

[0008] In order to achieve the above object, the production method of the present invention comprises the steps of: a chemical treatment step of contacting the pulp with a reaction solution containing sulfamic acid and urea and reacting the pulp at 120°C to 180°C to replace at least a portion of the hydroxyl groups of the cellulose constituting the pulp with sulfate ester groups; a refining step for refining the pulp after the chemical treatment step to obtain fine cellulose fibers; Including, In the reaction liquid, the amount of the sulfamic acid is 10 mmol to 48 mmol per 1 g of the pulp, and the molar ratio of the sulfamic acid (S) to the urea (U) is S:U=1:0.4 to 1:1.61; The pulp after the chemical treatment step is This is a method for producing fine cellulose fibers having a cellulose type I crystal structure, a degree of crystallinity of 76% or less, and a total light transmittance of 80% or more when dispersed in water at a solids concentration of 1% by mass. Effect of the Invention

[0009] According to the present invention, it is possible to provide a new method for producing fine cellulose fibers using pulp having a high total light transmittance in an aqueous dispersion. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 shows the X-ray diffraction peaks used to calculate the crystallinity of the sulfate ester group-introduced pulp (before defibration treatment) and the fine cellulose fibers (after 5 times of defibration treatment) in the examples. [Diagram 2] Fig. 2 shows a centrifuge tube in which an aqueous dispersion of fine cellulose fibers produced by the production method of the present invention is sealed, and a shaker in which the centrifuge tube is fixed on a top plate. Fig. 2A and Fig. 2B show photographs of the centrifuge tube and the shaker when observed from the horizontal and vertical directions, respectively.

[0011] Unless otherwise defined herein, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. All patents, applications and other publications and information referenced herein are incorporated herein by reference in their entirety. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] [Method of manufacturing fine cellulose fibers] The method for producing fine cellulose fibers of the present invention is a method for finely pulping pulp into which sulfate ester groups have been introduced (hereinafter referred to as "sulfate ester group-introduced pulp") obtained by subjecting pulp to a chemical treatment.

[0013] (Chemical treatment process) This step is a step of subjecting pulp to chemical treatment. Specifically, this step is a step of contacting pulp with a reaction solution containing sulfamic acid and urea and reacting at 120°C to 180°C to replace at least a part of the hydroxyl groups of the cellulose constituting the pulp with sulfate ester groups to obtain sulfate ester group-introduced pulp. In this step, the pulp may be contacted with a reaction solution containing sulfamic acid and urea and reacted at 120°C to 160°C.

[0014] In the present invention, "sulfate ester group-introduced pulp" refers to a fibrous member formed by the assembly of a plurality of cellulose fibers. The cellulose fibers have at least a portion of their hydroxyl groups substituted with sulfate ester groups. Specifically, the cellulose fibers have at least a portion of the hydroxyl groups (-OH groups) of the cellulose (a chain-like polymer in which D-glucose is bonded via β(1→4) glucoside bonds) that constitute the cellulose fibers substituted with sulfate ester groups represented by formula (1).

[0015] (-OSO3 - ) r Z r+ (1) In formula (1), r is an independent natural number from 1 to 7, Z r+ When r=1, it is at least one selected from the group consisting of a hydrogen ion, an alkali metal ion, a monovalent transition metal ion, an ammonium ion, an aliphatic ammonium ion, an aromatic ammonium ion, and a cationic polymer, and when r=2 or more, it is at least one selected from the group consisting of an alkaline earth metal ion, a polyvalent metal ion, and a compound containing two or more cationic functional groups (e.g., diamine, etc.) in the molecule.

[0016] This process (chemical treatment process) may include a contacting process in which pulp (e.g., wood-based pulp (hereinafter simply referred to as "wood pulp")) is contacted with a reaction liquid containing sulfamic acid and urea, and a reaction process in which the pulp after this contacting process is subjected to a heating reaction to substitute at least a portion of the hydroxyl groups of cellulose with sulfate ester groups.

[0017] In the present invention, pulp is a fibrous member in which a plurality of cellulose fibers are assembled. The cellulose fibers are an assembly of a plurality of fine fibers (for example, microfibrils, etc.). The fine fibers are an assembly of a plurality of cellulose molecules (hereinafter, sometimes simply referred to as cellulose), which are chain-like polymers in which D-glucose is bound by β(1→4) glycoside bonds. It is preferable to wash the pulp in advance. For example, by filtering and dehydrating the pulp using water on a 200 mesh or 235 mesh sieve, it is possible to sieve out fine fibers and debris that are too fine, which is desirable because it improves the handling during production. In other words, pulp is a fiber in which cellulose fibers of a size that can become residues on the 200 mesh or 235 mesh are assembled. The water may be tap water, but is preferably ion-exchanged water or pure water, and the same applies hereinafter.

[0018] Examples of the pulp include, but are not limited to, wood pulp, dissolving pulp, cotton pulp such as cotton linter, non-wood pulp such as wheat straw, bagasse, paper mulberry, mitsumata, hemp, kenaf, and fruit, and waste paper pulp prepared from used newspapers, used magazines, used cardboard, etc. From the viewpoint of availability, wood pulp is easy to use as the pulp.

[0019] There are various kinds of wood pulp, but the use is not particularly limited, and examples thereof include paper pulp such as softwood kraft pulp (NBKP), hardwood kraft pulp (LBKP), thermomechanical pulp (TMP), etc. The above pulp may be used alone or in combination of two or more kinds.

[0020] (Contact process) The contact step is a step of contacting the pulp with a reaction liquid containing sulfamic acid and urea. This contact step is not particularly limited as long as it is a method capable of causing the contact. For example, the pulp may be immersed in the reaction liquid containing sulfamic acid and urea to impregnate the pulp with the reaction liquid, or the reaction liquid may be applied to the pulp. Among these, if a method of immersing the pulp in the reaction liquid to impregnate the pulp with the reaction liquid is adopted, it is easy to uniformly contact the pulp with sulfamic acid and urea.

[0021] The solvent for dissolving sulfamic acid and urea is not particularly limited, and examples thereof include protic polar solvents such as water, ethanol, methanol, acetic acid, formic acid, 2-propanol, nitromethane, and aqueous ammonia, aprotic polar solvents such as acetone, ethyl acetate, tetrahydrofuran (THF), dimethylformamide (DMF), acetonitrile, dimethyl sulfoxide (DMSO), dimethyl sulfide (DMS), and dimethylacetamide (DMA), and non-polar solvents such as diethyl ether, benzene, toluene, hexane, chloroform, and 1,4-dioxane. The solvent may be used alone or in combination of two or more. In particular, water is preferred from the viewpoint of easily dissolving sulfamic acid and urea.

[0022] The pulp in this contacting state with the reaction solution containing sulfamic acid and urea in the contacting step is sometimes referred to as "reaction solution-impregnated pulp".

[0023] In the reaction solution containing sulfamic acid and urea, the amount of sulfamic acid is 10 mmol to 48 mmol per 1 g of pulp, and the molar ratio of sulfamic acid (S) to urea (U) is S:U=1:0.4 to 1:1.61, where "1 g of pulp" refers to the solid content mass, which is the dry mass of the pulp.

[0024] (State of pulp impregnated with reaction liquid) The state of the reaction liquid-impregnated pulp to be subjected to the above-mentioned next reaction step may be, for example, reaction liquid-impregnated pulp in its original state, i.e., in a state in which the pulp is in contact with the reaction liquid and no active water removal is performed, or in a state in which the pulp is in contact with the reaction liquid and the water has been actively removed, etc.

[0025] The former reaction liquid-impregnated pulp (in a state where water is not actively removed) includes pulp in a state where the pulp is in contact with the reaction liquid (including, for example, a slurry state, etc.), and pulp that is removed from the state where the pulp is in contact with the reaction liquid and allowed to stand to prepare the reaction liquid.

[0026] Meanwhile, the latter reaction liquid-impregnated pulp (in a state where moisture has been actively removed) refers to pulp that has been in contact with the reaction liquid and has had moisture intentionally removed from it. For example, it includes pulp that has been prepared by removing the pulp from the reaction liquid and pulp in contact and naturally drying it by air drying or the like, pulp that has been in contact with the reaction liquid and pulp and then filtered and dehydrated, pulp that has been contacted with the reaction liquid and then further dried by air drying, pulp that has been filtered and dehydrated and then further dried by using a circulating air dryer, pulp that has been filtered and dehydrated and then further dried by using a heating dryer, pulp that has been contacted with the reaction liquid and then dried by using a circulating air dryer or a heating dryer, and the like.

[0027] In this way, the reaction liquid-impregnated pulp to be subjected to the reaction step may be one that has not been subjected to the active water removal as described above, or one that has been subjected to active water removal to remove a certain amount of water. When the water is removed by drying, there is no problem even if the water content after drying is about 1%. In particular, by using the latter method, the water content in the reaction liquid-impregnated pulp to be subjected to the reaction step can be reduced, so that the reaction time in the heating reaction in the reaction step can be shortened. This has the advantage of improving the productivity of the sulfate ester group-introduced pulp. In addition, by using the method of performing a dehydration treatment, there is the advantage that the reaction liquid-impregnated pulp can be prepared more efficiently than when a large amount of reaction liquid is treated.

[0028] When an active drying method is used, the reaction liquid-impregnated pulp may be dried until its moisture content reaches about 1%, or the moisture may be removed by drying until the pulp reaches an absolutely dry state with a moisture content significantly lower than 1%.

[0029] In this specification, the term "wet state" refers to reaction liquid-impregnated pulp that has a moisture content of 1% or more and is not in an absolute dry state. For example, the term "wet state" may refer to pulp that is still impregnated with the reaction liquid, pulp that has been dehydrated to a certain extent, and pulp that has been dried to a certain extent.

[0030] In addition, in this specification, bone dry means a state in which the moisture content is reduced to less than 1% by, for example, reducing the pressure in a desiccator containing a desiccant such as calcium chloride or diphosphorus pentoxide, or by subjecting the material to a long-term heat drying treatment.

[0031] Therefore, when the latter method described above (a reaction method in which active moisture removal is performed) is used in the contact step, a method may be used in which the moisture content of the reaction liquid-impregnated pulp is brought to a non-bone-dry state, or a method may be used in which the moisture content is brought to a bone-dry state, but it is preferable to use a method in which the moisture content is brought to a non-bone-dry state.

[0032] In this specification, the moisture content of the reaction liquid-impregnated pulp is calculated using the following formula. Moisture content of reaction liquid-impregnated pulp (%) = 100 - (mass of solids in reaction liquid-impregnated pulp (g) / reaction liquid-impregnated pulp at the time of moisture content measurement (g)) x 100 = {(reaction liquid-impregnated pulp at the time of moisture content measurement (g) - mass of solids in reaction liquid-impregnated pulp (g)) / reaction liquid-impregnated pulp at the time of moisture content measurement (g)} x 100

[0033] The solid content mass (g) of the reaction solution-impregnated pulp in the above formula refers to the dry mass of the reaction solution-impregnated pulp. Specifically, it refers to the dry mass adjusted to a constant weight by drying the sample at 105°C using a dryer or the like. For example, the reaction solution-impregnated pulp is placed in a dryer and dried under specified drying conditions (e.g., 105°C, 2 hours) and the mass is measured, so that the mass of the reaction solution-impregnated pulp after moisture has been removed (i.e., the mass of the reaction solution-impregnated pulp that is not removed under the drying conditions. For example, the mass of the reaction solution-impregnated pulp that contains the reagents in the pulp and reaction solution) can be calculated. In addition, the constant weight refers to a state in which the moisture in the atmosphere in the treatment facility and the moisture in the raw material do not appear to flow in or out. Specifically, it refers to a state in which the change in the mass between two consecutive measurements after drying for a certain period of time (e.g., 2 hours) is within 1% of the mass at the start of drying (however, the second mass measurement should be at least half the drying time required for the first measurement).

[0034] The state of the pulp when it is brought into contact with the reaction liquid is not particularly limited, and may be, for example, in a dry state or a wet state (i.e., a moist state).

[0035] (Pre-drying process in the contact process) In the above example, the method for preparing the reaction liquid-impregnated pulp in the contact step was described, in which the reaction liquid-impregnated pulp is prepared by actively removing moisture. When using a method for removing moisture while heating (pre-drying step) in this method (for example, when the reaction liquid and the pulp are directly heated and dried in a contact state, or when the dehydrated pulp is heated and dried), it is desirable to adjust the heating temperature to a predetermined temperature or lower. The drying temperature in this pre-drying step is not particularly limited, but is preferably adjusted to a temperature at which the moisture contained in the reaction liquid-impregnated pulp and the moisture in the surroundings can be removed and the reaction does not proceed. For example, the drying temperature in the pre-drying step can be adjusted so that the atmospheric temperature of the reaction liquid-impregnated pulp is 100°C or lower. On the other hand, from the viewpoint of workability, it is preferable to adjust the temperature to 50°C or higher. Therefore, the drying temperature in the pre-drying step in the contact step is preferably 50°C to 100°C, or 70°C to 100°C.

[0036] (Moisture adjustment process in contact process) The contact step may include a moisture adjustment step in which the moisture content of the pulp to be contacted with the reaction liquid is adjusted to fall within a predetermined range. This moisture adjustment step is a step in which the pulp is adjusted by drying or humidifying so that the moisture content of the pulp is a predetermined moisture content. By including this moisture adjustment step, the moisture content in the pulp when it is contacted with the reaction liquid can be made somewhat uniform, which may improve product stability in continuous operation. In addition, there is an advantage in that if the pulp is dried to a certain extent to reduce the moisture content (for example, the moisture content is 1% to 10%), the storage property can be improved.

[0037] (Reaction process) As described above, the reaction liquid-impregnated pulp prepared in the contact step is provided to the next reaction step. This reaction step is a step in which the cellulose fiber contained in the reaction liquid-impregnated pulp provided from the contact step is reacted with the reaction liquid containing sulfamic acid and urea at 120°C to 180°C to replace at least a part of the hydroxyl groups in the cellulose fiber with sulfate ester groups of sulfamic acid, thereby introducing sulfate ester groups into the cellulose fiber contained in the pulp. That is, this reaction step is a step in which a reaction is carried out to replace at least a part of the hydroxyl groups in the cellulose fiber contained in the reaction liquid-impregnated pulp with sulfate ester groups.

[0038] The heater or the like used in the reaction step is not particularly limited, and for example, a heater capable of directly or indirectly heating the reaction liquid-impregnated pulp after the contact step while satisfying the above-mentioned requirements can be used, and a known dryer, reduced pressure dryer, microwave heating device, autoclave, infrared heating device, hot pressing method using a heat press machine (e.g., AH-2003C manufactured by AS ONE Co., Ltd.) can be used. In particular, from the viewpoint of operability, it is preferable to use a circulating air dryer since gas may be generated in the reaction step.

[0039] (Reaction time in the reaction process) The heating time in the reaction step (i.e., reaction time) is not particularly limited, but is, for example, 1 minute or more, 5 minutes or more, 10 minutes or more, or 15 minutes or more, and from the viewpoints of operability and cost, it is 5 to 300 minutes, or 5 to 120 minutes.

[0040] By carrying out the above steps, a pulp having sulfate ester groups introduced therein can be prepared.

[0041] (Cleaning process after reaction process) The chemical treatment process may include a washing step of washing the sulfate ester group-introduced pulp after the reaction step. The sulfate ester group-introduced pulp has an acidic surface due to the effect of sulfamic acid. In addition, unreacted reaction liquid is still present. For this reason, if a washing step is provided to completely terminate the reaction and remove excess reaction liquid to make the pulp neutral, the handling properties can be improved.

[0042] This washing step is not particularly limited, and may be any step that can make the sulfate ester group-introduced pulp nearly neutral. For example, a method of washing the sulfate ester group-introduced pulp with pure water or the like until it becomes neutral may be used. Neutralization washing may also be performed using an alkaline solution or the like. When performing such neutralization washing, examples of the alkaline compound contained in the alkaline solution include inorganic alkaline compounds and organic alkaline compounds. Examples of the inorganic alkaline compounds include hydroxides, carbonates, and phosphates of alkali metals. Examples of the organic alkaline compounds include ammonia, aliphatic amines, aromatic amines, aliphatic ammonium, aromatic ammonium, heterocyclic compounds, and hydroxides of heterocyclic compounds.

[0043] The method for separating the sulfate ester group-introduced pulp in the washing step is not particularly limited, and may be, for example, by filtering the sulfate ester group-introduced pulp and the washing water. For example, the sulfate ester group-introduced pulp after the reaction may be washed using a stainless steel sieve with an opening size of 243 μm (70 mesh) to 20 μm (635 mesh), 132 μm (120 mesh) to 45 μm (300 mesh), or 75 μm (200 mesh) to 45 μm (300 mesh).

[0044] [Physical properties of sulfate ester group-introduced pulp] The physical properties of the sulfate ester group-introduced pulp thus prepared are not particularly limited, but are, for example, as follows:

[0045] (Amount of sulfate ester group introduced) The amount of sulfate ester groups introduced per 1 g (solid mass) of sulfate ester group-introduced pulp is preferably adjusted to, for example, 0.8 mmol / g or more, 1 mmol / g or more, or 1.2 mmol / g or more.

[0046] Incidentally, the upper limit is not particularly limited, but from the viewpoint of suppressing fiber collapse and cost increase caused by decreased crystallinity, for example, the amount of sulfate ester groups introduced per 1 g (solid content mass) of sulfate ester group-introduced pulp is 9.9 mmol / g or less, 5 mmol / g or less.

[0047] In particular, from the viewpoint of transparency in a dispersion liquid dispersed in a dispersion medium, the amount of sulfate ester groups introduced into the sulfate ester group-introduced pulp is preferably adjusted to, for example, 0.8 mmol / g to 5 mmol / g, 1 mmol / g to 5 mmol / g, or 1.2 mmol / g to 5 mmol / g per 1 g (solid content mass) of the sulfate ester group-introduced pulp.

[0048] From the viewpoint of viscosity, the sulfate ester group-introduced pulp is preferably adjusted as follows. By setting the amount of sulfate ester groups introduced per 1 g (solid content mass) of sulfate ester group-introduced pulp within the following range, a decrease in viscosity in the dispersion can be suppressed. For example, the upper limit of the amount of sulfate ester groups introduced per 1 g (solid content mass) of sulfate ester group-introduced pulp is 3.5 mmol / g or less, 2 mmol / g or less. The lower limit is, for example, 1 mmol / g or more, 1.5 mmol / g or more. For example, in the sulfate ester group-introduced pulp, the amount of sulfate ester groups introduced per 1 g (solid content mass) of sulfate ester group-introduced pulp can be adjusted to 0.8 mmol / g to 3.5 mmol / g, 1 mmol / g to 2.5 mmol / g, or 1.5 mmol / g to 2 mmol / g.

[0049] The dispersion medium constituting the dispersion liquid of the sulfate ester group-introduced pulp is not particularly limited, but is preferably one that can exhibit the transparency and viscosity as described above. For example, the dispersion medium may be a protic polar solvent such as water, ethanol, methanol, acetic acid, formic acid, 2-propanol, nitromethane, or ammonia water; an aprotic polar solvent such as acetone, ethyl acetate, tetrahydrofuran (THF), dimethylformamide (DMF), acetonitrile, dimethyl sulfoxide (DMSO), dimethyl sulfide (DMS), or dimethylacetamide (DMA); or a non-polar solvent such as diethyl ether, benzene, toluene, hexane, chloroform, or 1,4-dioxane; one of these may be used alone, or two or more may be used in combination. From the viewpoint of handling, for example, a protic polar solvent such as water, ethanol, methanol, acetic acid, formic acid, or ammonia water may be used.

[0050] (Method for measuring the amount of sulfate ester groups introduced) The amount of sulfate ester groups introduced into the sulfate ester group-introduced pulp can be evaluated based on the amount of sulfur introduced due to the sulfate ester groups, or by directly measuring the sulfate ester groups. For example, the amount of sulfate ester groups introduced into the pulp can be measured using a CHNS / O elemental analyzer. The amount of sulfate ester groups introduced into the pulp can also be calculated by measuring electrical conductivity.

[0051] (Crystallization degree) The sulfate ester group-introduced pulp has a cellulose I-type crystal structure as a crystal structure, and the degree of crystallinity is 76% or less. Since the degree of crystallinity of the sulfate ester group-introduced pulp is 76% or less, the transparency of a dispersion liquid in which the sulfate ester group-introduced pulp is dispersed tends to be improved. From the viewpoint of maintaining the fiber shape, the degree of crystallinity of the sulfate ester group-introduced pulp is preferably 30% or more. From the viewpoint of viscosity, the degree of crystallinity of the sulfate ester group-introduced pulp is, for example, 75% or less, 70% or less, 65% or less, or 60% or less. Furthermore, from the viewpoint of handleability in the method for preparing the sulfate ester group-introduced pulp, the degree of crystallinity of the sulfate ester group-introduced pulp is, for example, 30% or more, or 40% or more.

[0052] The sulfate ester group-introduced pulp exhibits transparency even though it has a cellulose I type crystal structure as a crystal structure. That is, the sulfate ester group-introduced pulp has a function of exhibiting transparency even though it has a fibrous form of I type crystal structure. Here, water-soluble cellulose (e.g., carboxymethyl cellulose, hydroxypropyl cellulose, and cellulose sulfate) has been known as a cellulose exhibiting transparency. The crystal structures of these celluloses are all cellulose II type crystal structures, and do not have a fibrous structure. That is, the transparency of the conventional cellulose is exhibited by disintegrating the fibrous structure.

[0053] (Method of measuring crystallinity) The crystallinity of the sulfate ester group-introduced pulp can be measured, for example, by using an X-ray diffraction device.

[0054] When the amount of sulfate ester groups introduced into the sulfate ester group-introduced pulp and the degree of crystallinity are within the above-mentioned ranges, the transparency of a dispersion in which the sulfate ester group-introduced pulp is dispersed in a dispersion medium such as water can be improved.

[0055] The sulfate ester group-introduced pulp has an excellent viscosity due to, for example, a predetermined degree of crystallinity. Specifically, the viscosity of a pulp having a general I-type crystal structure is about several tens to several hundreds of mPa·s when measured by rotating at 6 rpm at 20°C for 3 minutes using a B-type viscometer, whereas the sulfate ester group-introduced pulp can exhibit an excellent viscosity (for example, several thousand mPa·s or more) that was not expected for conventional general pulps.

[0056] (transparency) The transparency in this specification can be evaluated, for example, by the total light transmittance (%), which evaluates the transparency of a liquid. Specifically, the transparency function of the sulfate ester group-introduced pulp can be evaluated by the total light transmittance (%) of a dispersion obtained by dispersing the sulfate ester group-introduced pulp in water. The sulfate ester group-introduced pulp is dispersed in water at a solid content concentration of 1 mass %, and the total light transmittance (%) of the dispersion is 80% or more, 85% or more, or 90% or more.

[0057] (Method for measuring total light transmittance) The total light transmittance can be measured, for example, using a spectroscopic haze meter.

[0058] The solids concentration in this specification can be calculated, for example, by using the following formula. Solid concentration (%) = (mass of solid content of sample (g)) / (amount of sample provided (g)) x 100

[0059] The "mass of solid content of the sample (g)" in the above formula refers to the dry mass of the sample. Specifically, it refers to the dry mass adjusted to a constant mass by drying the sample at 105°C using a dryer or the like. For example, the dispersion is placed in a dryer, dried under a specified drying condition (for example, at a temperature of 105°C for 2 hours), and measured, so that the dry mass of the sulfate ester group-introduced pulp as a sample in the dispersion can be calculated. In addition, the constant mass means a state in which the moisture in the atmosphere in the treatment facility and the moisture in the raw material do not appear to enter or leave. Specifically, it means a state in which the change in mass between two consecutive measurements after drying for a certain period of time (for example, 2 hours) is within 1% of the mass at the start of drying (however, the second mass measurement should be at least half the drying time required for the first measurement).

[0060] (average fiber length) The average fiber length of the sulfate ester group-introduced pulp is not particularly limited. For example, in order to improve the above-mentioned transparency, the average fiber length is 0.2 mm to 2 mm, 0.2 mm to 1.8 mm, 0.2 mm to 1.5 mm, or 0.2 mm to 1 mm.

[0061] (Short fiber rate (%)) Furthermore, in order to improve transparency, the sulfate ester group-introduced pulp may contain pulp having a short fiber length as described below. Examples of this short fiber length pulp (hereinafter referred to as "short fiber") include pulp having a fiber length of 0.04 mm or more and 0.2 mm or less in the fiber length distribution. The content (%) of short fibers in the sulfate ester group-introduced pulp (i.e., short fiber rate (%)) is, for example, 10% or more, 15% or more.

[0062] From the viewpoints of transparency and handleability, the sulfate ester group-introduced pulp has a short fiber content (%) (i.e., short fiber rate (%)) in terms of fiber length distribution of, for example, 10% to 70%, 10% to 60%, 10% to 50%, 10% to 45%, or 15% to 45%.

[0063] (average fiber width) The average fiber width of the sulfate ester group-introduced pulp is not particularly limited, and is, for example, 5 μm to 100 μm, 10 μm to 50 μm, 20 μm to 40 μm, or 20 μm to 30 μm.

[0064] (Fiber width distribution) In order to improve transparency, it is preferable that the sulfate ester group-introduced pulp has a high proportion of pulp with fiber widths of 1 μm to 40 μm, 1 μm to 30 μm, and 1 μm to 20 μm in its fiber width distribution.

[0065] (Method of measuring average fiber length, average fiber width and fiber distribution) The average fiber length and average fiber width of the sulfate ester group-introduced pulp can be measured, for example, using a fiber tester or fiber length distribution measuring instrument manufactured by Lorentzen & Wettley in accordance with ISO 16065-2: 2007. The fiber length distribution and fiber width distribution of the sulfate ester group-introduced pulp can be measured, for example, using a fiber length distribution measuring instrument in accordance with ISO 16065-2: 2007.

[0066] (Kink) In order to improve transparency, it is preferable that the sulfate ester group-introduced pulp has little bending. Specifically, it is preferable that the sulfate ester group-introduced pulp has a low kink (1 / m) value. For example, the sulfate ester group-introduced pulp has a kink (1 / m) of 1 to 300, 1 to 100, or 1 to 50.

[0067] (Method of measuring kink) The kink of the sulfate ester group-introduced pulp can be measured, for example, using a fiber length distribution measuring device in accordance with ISO 16065-2:2007.

[0068] From the viewpoint of reliability of the measured values ​​of the sulfate ester group-introduced pulp, it is desirable to measure at least 5,000 fibers in accordance with ISO 16065-2: 2007. Moreover, the number of fibers contained in the sulfate ester group-introduced pulp is desirably 5,000 or more and 70,000 or less per 0.1 g of solid content.

[0069] (viscosity) When the degree of crystallinity of the sulfate ester group-introduced pulp is equal to or less than the aforementioned value, for example, the dispersion has a predetermined viscosity. For example, when the degree of crystallinity of the sulfate ester group-introduced pulp is 70% or less, the viscosity of the dispersion in which the sulfate ester group-introduced pulp is dispersed in water is 1000 mPa·s or more, 5000 mPa·s or more, or 10000 mPa·s or more. In particular, when the degree of crystallinity of the sulfate ester group-introduced pulp is 60% or less, the viscosity of the dispersion tends to be improved. Furthermore, when the average fiber length is 1 mm or less, this tendency becomes stronger.

[0070] (Method of measuring viscosity) The viscosity (mPa s) of the sulfate ester group-introduced pulp can be measured, for example, using a B-type viscometer at a measurement temperature of 20°C, with the measurement being performed at rotation speeds of 6 rpm and 60 rpm. The thixotropy index (TI) value can also be calculated from each viscosity value. TI value = (viscosity at 6 rpm) / (viscosity at 60 rpm)

[0071] The TI value can be adjusted as appropriate, and when a high TI value is required, the lower limit of the TI value is, for example, 3 or more, 4 or more, or 5 or more. The upper limit of the TI value is, for example, 10 or less, 8 or less, 6 or less, or 5 or less. On the other hand, when a low TI value is preferred, the lower limit is, for example, 1 or more, and the upper limit is, for example, 3 or less, or 2.5 or less.

[0072] (Micronization process) This step is a step of pulp having sulfate ester groups introduced therein is pulverized to produce fine fibers of a predetermined size (for example, nano-level). The processing device used in this step is not particularly limited as long as it has the above-mentioned function. For example, the processing device may be, but is not limited to, a low-pressure homogenizer, a high-pressure homogenizer, a grinder (stone-type grinder), a ball mill, a cutter mill, a jet mill, a single-screw extruder, a twin-screw extruder, an ultrasonic agitator, a household mixer, or the like. Of these, it is desirable to use a high-pressure homogenizer, since it can apply force evenly to the material and is excellent in homogenization.

[0073] In this step, when a high-pressure homogenizer is used, the sulfate ester group-introduced pulp is supplied in a state of being dispersed in an aqueous dispersion medium such as water. In the following, the dispersion liquid in which the sulfate ester group-introduced pulp is dispersed may be referred to as a slurry. The solid content concentration of the sulfate ester group-introduced pulp in this slurry is not particularly limited, and is, for example, 0.1% by mass to 20% by mass.

[0074] For example, if a slurry in which the solid content of sulfate ester group-introduced pulp has been adjusted to 0.5% by mass is fed to a processing device such as a high-pressure homogenizer, a dispersion liquid in which fine cellulose fibers having the same solid content are dispersed in an aqueous dispersion medium can be obtained. That is, in this case, a dispersion liquid with a solid content of 0.5% by mass can be obtained.

[0075] The water retention of the sulfate ester group-introduced pulp to be subjected to this step is not particularly limited, but is preferably adjusted so as to be easily pulverized by the above-mentioned device. For example, from the viewpoint of the efficiency of pulverization and the reduction of energy used, it is desirable to use sulfate ester group-introduced pulp prepared to have a high water retention. From this viewpoint, it is preferable to use sulfate ester group-introduced pulp prepared to have a water retention of 150% or more, 200% or more, 250% or more, 300% or more, or 500% or more. From the viewpoint of the recovery rate of fine cellulose fibers, the water retention is, for example, 10000% or less. Thus, from the viewpoint of the pulverization efficiency and the recovery rate, the water retention of the sulfate ester group-introduced pulp to be subjected to this step is 150% to 10000%, 200% to 10000%, 220% to 10000%, 250% to 5000%, or 250% to 2000%.

[0076] [Microfine cellulose fiber] According to the production method of the present invention, by pulp satisfying the above-mentioned characteristics after the chemical treatment step, fine cellulose fibers can be obtained whose viscosity is reduced by slightly shaking the dispersion. The fine cellulose fibers produced by the production method of the present invention (hereinafter, sometimes referred to as "fine cellulose fibers of the present invention") have excellent handleability because the viscosity is reduced by, for example, the impact when the dispersion is poured into a container. Specifically, the fine cellulose fibers of the present invention may have a viscosity μ1 of 100,000 mPa·s or less, measured by sealing 100 g of a 1% by mass aqueous dispersion of the fine cellulose fibers in a 100 mL centrifuge tube, leaving it at 20°C for 24 hours, shaking it at 300 rpm at 20°C in a substantially horizontal direction for 5 minutes or more, and then rotating it at 1 rpm at 20°C for 3 minutes using a B-type viscometer.

[0077] The lower limit of the viscosity μ1 is not particularly limited, but is, for example, 20,000 mPa·s or more. The viscosity μ1 may be, for example, 20,000 mPa·s to 100,000 mPa·s, 30,000 mPa·s to 100,000 mPa·s, 40,000 mPa·s to 100,000 mPa·s, 50,000 mPa·s to 100,000 mPa·s, or 60,000 mPa·s to 100,000 mPa·s.

[0078] Any centrifuge tube may be used, for example, Model No. 2355-100N manufactured by AGC Technos IWAKI Co., Ltd. The shaking is preferably performed using a shaker, for example, Lab Shaker (reciprocating motion) (Model No. SR-1) manufactured by AS ONE Co., Ltd.

[0079] It is preferable to start the measurement of the viscosity μ1 within 5 seconds after the shaking is stopped for the following reasons: the viscosity μ1 gradually returns to the original viscosity before shaking as time passes after the shaking is stopped, the reliability of the measured value is ensured by making the measurement conditions as uniform as possible between samples, and a certain amount of time is actually required for the experimental operation.

[0080] The fine cellulose fibers of the present invention may have a viscosity μ0 of 170,000 mPa s or more when a 1% by mass aqueous dispersion of the fibers is sealed in the centrifuge tube, allowed to stand at 20°C for 24 hours, and then rotated at 1 rpm at 20°C for 3 minutes without shaking using a B-type viscometer.

[0081] In the fine cellulose fiber of the present invention, the viscosities μ1 and μ0 satisfy the following formula (2): 0.1≦μ1 / μ0≦0.5 (2) The above condition may be satisfied.

[0082] The fine cellulose fibers of the present invention can have improved hydrophilicity by having sulfate ester groups. That is, by introducing sulfate ester groups into the fine cellulose fibers, the dispersibility of the fine cellulose fibers when dispersed in a dispersion liquid can be improved. Moreover, the electronic repulsion of the introduced sulfate ester groups makes it easier to maintain the dispersed state in the dispersion liquid.

[0083] In addition, the fine cellulose fibers can be imparted with a physiological activity derived from sulfate ester groups. For example, chondroitin sulfate, a type of sulfated polysaccharide known as a heparin-like substance, has hyaluronidase inhibitory activity and skin moisturizing activity, and therefore its application to xerosis, asteatosis, and atopic dermatitis is being considered. The fine cellulose fibers of the present invention can also be used in the medical field based on the physiological activity derived from sulfate ester groups.

[0084] The dispersion medium of the dispersion liquid is not particularly limited. For example, as an aqueous dispersion medium, water, alcohol, ketone, amine, carboxylic acid, ether, amide, or a mixture thereof may be used.

[0085] (Amount of sulfate ester groups introduced into fine cellulose fibers) The amount of sulfuric acid ester groups introduced into the fine cellulose fiber of the present invention can be expressed as the amount of sulfur introduced based on the sulfate ester groups, and is not particularly limited, but is preferably within a range in which transparency and dispersibility can be maintained to a certain degree. The amount of sulfur introduced per 1 g (mass) of the fine cellulose fiber of the present invention is, for example, higher than 0.4 mmol / g, and is 0.42 mmol / g to 9.9 mmol / g, 0.5 mmol / g to 9.9 mmol / g, or 0.6 mmol / g to 9.9 mmol / g.

[0086] If the amount of sulfur introduced is more than 0.42 mmol / g, the hydrogen bonds between the fibers do not become too strong, and dispersibility tends to improve, and if it is 0.5 mmol / g or more, the electronic repulsion can be made stronger, making it easier to maintain a stable dispersed state. On the other hand, if the amount of sulfur introduced is 9.9 mmol / g or less, the decrease in crystallinity and the increase in cost when introducing sulfur can be suppressed.

[0087] In particular, when attention is paid to maintaining dispersibility and transparency, the amount of sulfur introduced is, for example, more than 0.42 mmol / g and not more than 3 mmol / g, 0.5 mmol / g to 3 mmol / g, 0.5 mmol / g to 2 mmol / g, or 0.5 mmol / g to 1.5 mmol / g.

[0088] (Method for measuring the amount of sulfate ester groups introduced) The amount of sulfur introduced into the fine cellulose fiber of the present invention (i.e., the amount of sulfate ester groups introduced) can be measured using a CHNS / O elemental analyzer. The amount of sulfur introduced can also be calculated by measuring electrical conductivity. When the fine cellulose fiber is prepared from sulfate ester group-introduced pulp, the amount of sulfur introduced into the fine cellulose fiber may be calculated from the amount of sulfur introduced into the pulp.

[0089] The average fiber length and average fiber width of the fine cellulose fiber of the present invention are not particularly limited, but are preferably adjusted so that the fibers are easily entangled with each other and are easily transparent when dispersed in an aqueous dispersion medium.

[0090] (Average fiber length of fine cellulose fibers) The average fiber length of the fine cellulose fibers of the present invention can be indirectly expressed, for example, by the degree of polymerization. The average fiber length of the fine cellulose fibers of the present invention is, for example, 280 or more, 300-1000, or 300-600 in terms of the degree of polymerization.

[0091] When the degree of polymerization of the fine cellulose fiber of the present invention is 280 or more, it is possible to prevent the fiber from becoming weakly entangled due to a decrease in fiber length. On the other hand, when the degree of polymerization of the fine cellulose fiber of the present invention is 600 or less, the fiber has high dispersibility, and when slurried, the slurry viscosity does not become too high, resulting in high dispersion stability and excellent handleability.

[0092] (Method of measuring degree of polymerization) The method for measuring the degree of polymerization is not particularly limited, but for example, the copper ethylenediamine method can be used. Specifically, the degree of polymerization of the fine cellulose fiber of the present invention can be measured by dissolving the fine cellulose fiber of the present invention in a 0.5 M copper ethylenediamine solution and measuring the viscosity of the solution by a viscometer.

[0093] (Average fiber width of fine cellulose fibers) The average fiber width of the fine cellulose fiber of the present invention is not particularly limited, but is preferably a width that easily provides transparency when dispersed in an aqueous dispersion medium. The average fiber width of the fine cellulose fiber of the present invention is, for example, 1 nm to 1000 nm, 2 nm to 500 nm, 2 nm to 100 nm, 2 nm to 30 nm, or 2 nm to 20 nm when observed with an electron microscope.

[0094] If the average fiber width is 1 nm or more, the physical properties (strength, rigidity, dimensional stability, etc.) of fine cellulose fibers are easily exhibited when dispersed in water as cellulose molecules. On the other hand, if the average fiber width is 1000 nm or less, the physical properties (transparency, strength, rigidity, dimensional stability, etc.) of fine cellulose fibers tend to be easily obtained.

[0095] In particular, from the viewpoint of applications requiring ease of handling and transparency, the average fiber width is, for example, within the following range. If the average fiber width is less than 30 nm, the aspect ratio does not decrease, and there is a tendency to avoid a decrease in entanglement between fibers. Furthermore, if the average fiber width is less than 30 nm, it is far from 1 / 10 of the wavelength of visible light, and when combined with a matrix material, refraction and scattering of visible light are unlikely to occur at the interface, and scattering of visible light does not occur, and transparency tends to increase. Therefore, from the viewpoint of ease of handling and transparency, the average fiber width of the fine cellulose fiber of the present invention is, for example, 2 nm to 30 nm, 2 nm to 20 nm, or 2 nm to 10 nm. In particular, from the viewpoint of transparency, the average fiber width of the fine cellulose fiber of the present invention is, for example, 20 nm or less, or 10 nm or less. If the average fiber width is 10 nm or less, scattering of visible light can be reduced, and therefore fine cellulose fibers having high transparency can be obtained.

[0096] (Method of measuring average fiber width) The average fiber width of the fine cellulose fibers of the present invention can be measured using a known technique. For example, fine cellulose fibers are dispersed in a dispersion medium such as pure water to prepare a dispersion liquid with a predetermined mass %. Then, this dispersion liquid is spin-coated on a silica substrate coated with PEI (polyethyleneimine), and the fine cellulose fibers on the silica substrate are observed. For example, a scanning probe microscope (for example, SPM9700 manufactured by Shimadzu Corporation) can be used as an observation method. The average fiber width of the fine cellulose fibers can be obtained by randomly selecting 20 fine cellulose fibers in the obtained observation image, measuring the fiber width of each fiber, and averaging them.

[0097] (Haze value) The transparency when visually observing a dispersion liquid adjusted to a predetermined solid content concentration of the fine cellulose fibers of the present invention can be evaluated by the haze value. The solid content concentration is not particularly limited, but is, for example, 0.1% by mass to 20% by mass. From the viewpoint of transparency, it is preferable that the haze value of such a dispersion liquid is 20% or less. When the solid content concentration is 0.2% by mass to 0.5% by mass, the haze value of this dispersion liquid is, for example, 20% or less, 15% or less, or 10% or less.

[0098] The dispersion medium of the dispersion liquid is, for example, an aqueous dispersion medium. Examples of the aqueous dispersion medium that can be used include water, alcohol, ketone, amine, carboxylic acid, ether, amide, and mixtures thereof.

[0099] (Method of measuring haze value) The haze value can be measured, for example, as follows. First, fine cellulose fibers are dispersed in the dispersion medium to a predetermined solid content concentration. Then, the haze value can be obtained by measuring the dispersion liquid using a spectrophotometer in accordance with JIS K 7105.

[0100] (Total light transmittance) The total light transmittance of the dispersion is, for example, 90% or more, 95% or more, within the haze value range. The total light transmittance can be measured, for example, as follows. First, fine cellulose fibers are dispersed in the dispersion medium to a predetermined solid content concentration. Then, the total light transmittance can be obtained by measuring the dispersion using a spectrophotometer in accordance with JIS K 7105. EXAMPLES

[0101] [Example 1-1] Preparation of sulfate ester group-introduced pulp (Pulp pretreatment) Softwood bleached kraft pulp (NBKP) (hereinafter simply referred to as "pulp") with an average fiber length of 2.54 mm manufactured by Marusumi Paper Co., Ltd. was washed with a large amount of ion-exchanged water, and then the water was removed using a sieve with an opening of 75 μm (200 mesh) to obtain wet pulp (hereinafter referred to as "wet pulp") with a solid content concentration of 25.0 mass% that had never been dried. The ion-exchanged water used had an electrical conductivity of 0.1 to 0.2 μS / cm as measured using an ion-exchanged water generator (model number: G-5DSTSET) manufactured by Organo Corporation, and hereafter this will be referred to as pure water.

[0102] (Chemical treatment process) Sulfamic acid and urea were added to a 1 L beaker containing 600 mL of pure water so that the amount of sulfamic acid was 12.4 mmol per 1 g of the wet pulp to be added later, and the molar ratio of sulfamic acid (S) and urea (U) was S:U = 1:0.80, and then the mixture was stirred at room temperature until completely dissolved to prepare a reaction solution. As the sulfamic acid, 99.8% purity manufactured by Fuso Chemical Co., Ltd. was used, and as the urea, 99.0% purity, model number: special grade reagent manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. was used. 400 g of the wet pulp was added to the obtained reaction solution and impregnated for about 10 minutes (contact step).

[0103] (Reaction liquid impregnated pulp to be subjected to reaction process) The reaction liquid-impregnated pulp to be subjected to the next reaction step was prepared as follows. First, the pulp impregnated with the reaction liquid was spread on an aluminum tray. Next, the aluminum tray was placed in a dryer in an atmosphere of 85°C and dried to prepare the reaction liquid-impregnated pulp. The moisture content of the reaction liquid-impregnated pulp was 5% or less.

[0104] (Reaction process) The reaction solution-impregnated pulp was subjected to a heating reaction using a dryer. The temperature of the thermostatic chamber of the dryer was 120°C, and the heating time was 30 minutes. The reaction solution-impregnated pulp after heating was washed until it became neutral, to prepare a sulfate ester group-introduced pulp. The washing was carried out by adding a large amount of pure water to the reacted pulp to make a slurry, and then adding sodium hydrogen carbonate (manufactured by Nacalai Tesque, Inc., purity 99.5%) until no bubbles were generated to neutralize the slurry (washing step after the reaction step). The washing was carried out on a 300 mesh sieve (mesh opening 45 μm, manufactured by Sanpo Co., Ltd.).

[0105] Preparation of fine cellulose fibers The sulfate ester group-introduced pulp was subjected to defibration treatment five times using a high-pressure homogenizer (Yoshida Kikai Kogyo Co., Ltd., "Nano-Veita", pressure: 60 MPa) to obtain a 1% by mass aqueous dispersion of fine cellulose fibers.

[0106] [Examples 1-2 to 5-4, Reference Examples 6-1 to 6-4, and Comparative Examples 1-1 to 7-7] Except for the temperature of the thermostatic bath of the dryer in the reaction process, the amount of sulfamic acid (mmol) per gram of pulp in the wet pulp, and the molar ratio of sulfamic acid and urea as shown in Tables 1 to 7, 1 mass% aqueous dispersions of fine cellulose fibers of Examples 1-2 to 5-4, Reference Examples 6-1 to 6-4, and Comparative Examples 1-1 to 7-7 were obtained in the same manner as in Example 1-1.

[0107] [Table 1] [Table 2] [Table 3] [Table 4] [Table 5] [Table 6] [Table 7]

[0108] Tables 1 to 7 show the experimental results when the temperature of the thermostatic chamber of the dryer in the reaction step was 120°C, 130°C, 140°C, 150°C, 160°C, 180°C and 200°C, respectively. In addition, "carbonized" in the table indicates that the sulfate ester group-introduced pulp obtained in the manufacturing process of the fine cellulose fiber turned black and did not function as a pulp fiber, and "low yield" in the table indicates that the pulp was not carbonized but had a recovery yield of 30% or less on a 300 mesh sieve. In addition, "A" in the table indicates that there is a viscosity-thinning property based on the following judgment criteria, "B" in the table indicates that the viscosity-thinning property may be present but a sample could not be prepared due to low yield, and "C" in the table indicates that the viscosity-thinning property is not present (or it is predicted that there is no viscosity-thinning property even though it was not measured). In addition, "-" in the table indicates that the measurement was not performed. <Criteria for determining whether or not there is viscosity-thinning property> - Viscosity μ1 is 100,000 mPa·s or less. - Viscosity μ0 is 170,000 mPa·s or more. Viscosity μ1 and μ0 satisfy 0.1≦μ1 / μ0≦0.5.

[0109] [Evaluation of sulfate ester group-introduced pulp] The crystallinity of the sulfate ester group-introduced pulp prepared in the production process of the fine cellulose fibers of the Examples and Comparative Examples was measured using an X-ray diffractometer. The crystallinity was calculated according to the following formula. Crystallinity (%) = (22.4° strength - 18.5° strength) / 22.4° strength x 100

[0110] As a result, the sulfate ester group-introduced pulp prepared in the production process of the fine cellulose fiber of the Examples had a cellulose I type crystal structure, and its crystallinity was 76% or less. For example, the crystallinity of the sulfate ester group-introduced pulp prepared in the production process of the fine cellulose fiber of Examples 3-4 was 75.2 as calculated by the above formula based on the 22.4° intensity and 18.5° intensity values ​​in the graph shown in Figure 1. Note that in Reference Examples 6-1 to 6-4, the yield was low and the calculation results of the crystallinity could not be obtained, but it was thought to be 76% or less.

[0111] Moreover, the total light transmittance of the sulfate ester group-introduced pulp prepared in the production process of the fine cellulose fibers of the Examples and Comparative Examples was measured using a spectrophotometer in accordance with JIS K 7105.

[0112] As a result, the sulfate ester group-introduced pulp prepared in the manufacturing process of the fine cellulose fiber of the Examples had a total light transmittance of 80% or more when dispersed in water at a solid content concentration of 1% by mass. In Reference Examples 6-3 and 6-4, the yield was low and the total light transmittance could not be measured, but it was thought to be 80% or more.

[0113] In addition, the sulfate ester group-introduced pulps prepared in the production process of the fine cellulose fibers of Comparative Examples 1-4, 2-4, 3-3, 3-7, 4-5, 5-4, 6-4 and 7-1 to 7-7 were carbonized from the start and could not be used for any measurement.

[0114] [Evaluation of fine cellulose fibers] The transparency (haze value) of the 1 mass % aqueous dispersion of the fine cellulose fibers of the Examples and Comparative Examples was determined by measuring the transparency (haze value) of the 1 mass % aqueous dispersion of the fine cellulose fibers using a spectrophotometer in accordance with JIS K 7105.

[0115] The crystallinity of the fine cellulose fibers of the examples and comparative examples was measured and calculated in the same manner as in the case of the sulfate ester group-introduced pulp described above. For example, the crystallinity of the fine cellulose fibers of Example 3-4 was 56.2 as calculated by the above formula based on the 22.4° intensity and 18.5° intensity values ​​in the graph shown in Figure 1.

[0116] Viscosity measurement of fine cellulose fibers 100 g of a 1% by mass aqueous dispersion of the fine cellulose fibers of the Examples and Comparative Examples was sealed in a centrifuge tube (AGC Technoglass IWAKI, model number: 2355-100N, capacity: 100 mL, body material: PP (polypropylene), cap material: HDPE (high density polyethylene), size: 45 mm x 104 mm).

[0117] The conditions for measuring the viscosity of the aqueous dispersion are as follows. B-type viscometer (manufactured by Eiko Seiki Co., Ltd., model number: DV2T) Measurement conditions: 20° C., rotation at 1 rpm for 3 minutes, RV-05 spindle, single point data recording method.

[0118] The single point is a setting for the recording method that only obtains the value at the end of the measurement in the Brookfield viscometer. In other words, the instantaneous value 3 minutes after the start of the measurement is recorded.

[0119] The shaking conditions of the centrifuge tube in which the aqueous dispersion was sealed were as follows. First, the viscosity (μ0) was measured when the centrifuge tube was left standing at 20° C. for 24 hours without shaking. After the centrifuge tube was left standing at 20° C. for 24 hours without shaking, the centrifuge tube was fixed to the top plate of a shaker (lab shaker (reciprocating motion), AS ONE Corporation, model number: SR-1) so that the direction of the main body (the direction perpendicular to the top surface of the cap when the cap of the centrifuge tube is closed) coincided with the direction of horizontal shaking (FIG. 2), and the tube was subjected to horizontal shaking for 10 minutes (20° C., 300 rpm (device scale 10)), and the viscosity (μ1) after the shaking was measured. The measurement of viscosity μ1 was started within 5 seconds after the shaking was stopped.

[0120] The results are shown in Tables 1 to 7. It was found that the fine cellulose fibers of Examples 1-1 to 1-3, 2-1 to 2-3, 3-1 to 3-6, 4-1 to 4-2, and 5-1 to 5-3 have viscosity reducing properties. Therefore, it was found that the fine cellulose fibers of these Examples have excellent handleability because the viscosity of the fine cellulose fibers of these Examples is reduced by slightly shaking the 1% by mass aqueous dispersion thereof.

[0121] The various features of the present invention described herein can be combined in various ways, and all aspects obtained by such combinations, including combinations not specifically described herein, are within the scope of the present invention. In addition, those skilled in the art will understand that many different modifications are possible without departing from the spirit of the present invention, and equivalents including such modifications are also included in the scope of the present invention. Therefore, it should be understood that the embodiments described herein are merely examples and are not intended to limit the scope of the present invention.

Claims

1. a chemical treatment step of contacting pulp with a reaction solution containing sulfamic acid and urea and reacting the pulp at 120°C to 180°C to replace at least a portion of the hydroxyl groups of the cellulose constituting the pulp with sulfate ester groups; a refining process for refining the pulp after the chemical treatment process to obtain fine cellulose fibers; Including, In the reaction liquid, the amount of the sulfamic acid is 10 mmol to 48 mmol per 1 g of the pulp, and the molar ratio of the sulfamic acid (S) to the urea (U) is S:U=1:0.4 to 1:1.61; The pulp after the chemical treatment step is A method for producing fine cellulose fibers, the fine cellulose fibers having a cellulose I type crystal structure, a degree of crystallinity of 76% or less, and a total light transmittance of a dispersion liquid obtained by dispersing the fine cellulose fibers in water at a solid content concentration of 1% by mass of the fine cellulose fibers being 80% or more.

2. 2. The method for producing fine cellulose fibers according to claim 1, wherein in the chemical treatment step, the pulp is contacted with a reaction solution containing sulfamic acid and urea and reacted at 120°C to 160°C.

3. 100 g of the 1% by mass aqueous dispersion of the fine cellulose fibers was sealed in a 100 mL centrifuge tube, left to stand at 20° C. for 24 hours, shaken at 300 rpm at 20° C. in a substantially horizontal direction for 5 minutes or more, and then rotated at 1 rpm at 20° C. for 3 minutes using a B-type viscometer to measure the viscosity μ 1 is 100,000 mPa s or less, The 1% by mass aqueous dispersion of the fine cellulose fibers was sealed in the centrifuge tube, allowed to stand at 20° C. for 24 hours, and then rotated at 20° C. and 1 rpm for 3 minutes without shaking using a B-type viscometer to measure the viscosity μ 0 is 170,000 mPa s or more, and The viscosity μ 1 and μ 0 is expressed by the following formula (2): 0.1≦μ 1 / m 0 ≦0.5 (2) The method for producing fine cellulose fibers according to claim 1 or 2, which satisfies the above.

Citation Information

Patent Citations

  • Production method of cellulose nanofiber and production apparatus of cellulose nanofiber

    JP2017008472A

  • Method for producing cellulose nanofiber

    JP2017025240A

  • Phosphorylated fine cellulose fiber and production method thereof

    JP2017025468A

  • Method for producing cellulose nanofiber

    JP2017043677A

Cited By

  • Dispersion, composite, and producing methods therefor

    US20240183107A1